(untitled) (Research, Society and Development, 2022)
Art therapy is a method that aims to provide mental health and its practice incorporates different artistic languages. In this article, the objective was to compare the experience of the protagonist of the film Like Stars on Earth, the person with dyslexia Ishaan, and the dyslexia patient Clarice, in order to understand the importance of art therapy as an ally in psychotherapeutic intervention. We also aim to understand how the institutionalization of the current educational system interferes with inclusive education, interfering with the development of noogenic neurosis in students with dyslexia. In this context, the role of the family as an institution is also preponderant in promoting awareness and valuing the unique ways in the teaching-learning process of dyslexia patients. From the proposition of Paradoxal Intention Therapy associated with therapeutic art resources, we proposed an intervention in the Clarice case, having art as an ally in the dawn of the meaning of life. We hope that this work can enhance unique ways of the free creation-learning process, especially from Ishaan’s outcome, providing changes in the affective, interpersonal and relational spheres of students with dyslexia.